G-20 Data Gaps Initiative II : Meeting the Policy Challenge - Heath, Robert (IMF Working Papers; Working Paper ;, 2016)
The G-20 Data Gaps Initiative (DGI), which aimed at addressing the information needs that were revealed by the 2007/2008 global financial crisis, concluded its first phase and started a second phase (DGI-2) with the endorsement of G-20 Finance Ministers and Central Bank Governors in September 2015. The DGI-2 recommendations maintain the continuity of DGI-1 but reflecting the evolving policy needs focus more on datasets that support the monitoring of risks in the financial sector and the analysis of the inter-linkages across the economic and financial systems. The paper presents the DGI as an overarching initiative, bringing together various statistical frameworks for a complete picture of the economic and financial system to support the work of policy makers.